2000
DOI: 10.1105/tpc.12.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the SAAT Gene Involved in Strawberry Flavor Biogenesis by Use of DNA Microarrays

Abstract: Fruit flavor is a result of a complex mixture of numerous compounds. The formation of these compounds is closely correlated with the metabolic changes occurring during fruit maturation. Here, we describe the use of DNA microarrays and appropriate statistical analyses to dissect a complex developmental process. In doing so, we have identified a novel strawberry alcohol acyltransferase ( SAAT ) gene that plays a crucial role in flavor biogenesis in ripening fruit. Volatile esters are quantitatively and qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
317
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(331 citation statements)
references
References 39 publications
12
317
1
1
Order By: Relevance
“…Alcohol acyl transferases (AAT) are capable of combining various alcohols and acyl CoAs, resulting in the synthesis of a wide range of esters, thus accounting for the diversity of esters. Numerous AAT genes have been isolated and characterized in fruit and vegetables (Aharoni et al, 2000;Beekwilder et al, 2004;El-Sharkawy et al, 2005). Aliphatic esters contribute to the aroma of nearly all fruits and are emitted by vegetative tissues.…”
Section: Fatty Acid-derived and Other Lipophylic Flavor Compoundsmentioning
confidence: 99%
“…Alcohol acyl transferases (AAT) are capable of combining various alcohols and acyl CoAs, resulting in the synthesis of a wide range of esters, thus accounting for the diversity of esters. Numerous AAT genes have been isolated and characterized in fruit and vegetables (Aharoni et al, 2000;Beekwilder et al, 2004;El-Sharkawy et al, 2005). Aliphatic esters contribute to the aroma of nearly all fruits and are emitted by vegetative tissues.…”
Section: Fatty Acid-derived and Other Lipophylic Flavor Compoundsmentioning
confidence: 99%
“…Only recently, it was shown that the SAAT (for strawberry alcohol acylCoA transferase) and FaNES (for Fragaria 3 ananassa nerolidol synthase) genes are involved in strawberry fruit ester and terpene formation, respectively (Aharoni et al, 2000(Aharoni et al, , 2004 and that FaOMT (for Fragaria 3 ananassa O-methyltransferase) encodes an O-methyltransferase responsible for DMMF biosynthesis Wein et al, 2002). The first indications for the enzymatic formation of HDMF in strawberry fruit were provided by studies demonstrating the correlation of fruit ripening stage and HDMF concentration (Sanz et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It is most efficient in the analysis of intermediate and secondary metabolisms which are well characterised to be subject to strong transcriptional control 1,5,11,16 . In some examples, co-expression analysis succeeded to be performed in sulfur assimilation, genes for β-oxidation, branched-chain amino acid degradation, chlorophyll breakdown, and the lysine catabolism 3 , cell wall metabolism 10,7 and light signalling cascade 14 .…”
Section: Discussionmentioning
confidence: 99%